Public attitudes toward COVID-19 misbehaviors: Perceived seriousness of the misbehavior and perceived severity of the appropriate punishment - Levy, Inna; Cohen-Louck, Keren; Herzog, Sergio (Frontiers in Psychology, 2023)
Purpose: This interdisciplinary study explores attitudes toward health-related misbehaviors from a criminological point of view by comparing attitudes toward COVID-19 misbehaviors to the attitudes toward reckless behaviors related to driving and HIV (Human Immunodeficiency Virus) patients' sexual behavior and identifying the predictors of attitudes toward COVID-19 misbehaviors. Methods: An online factorial survey included 679 respondents aged 18 to 89 years. The participants read various scenarios related to the violation of COVID-19 restrictions, reckless sexual behavior among HIV patients, and reckless driving. The participants evaluated the seriousness of each behavior and the appropriate severity of the punishment in each scenario. Within the scenarios about COVID-19 misbehaviors, we manipulated such variables as the type of COVID-19 misbehavior and violators' gender, ethnicity, and religiosity. Additionally, participants answered questions about their demographic characteristics, vaccination, fear of COVID-19, and perceived contribution of COVID-19 misbehaviors to COVID-19-related morbidity. Results: The results indicated that participants perceived COVID-19 misbehaviors as less serious (Mean=8.11, S.D.=2.49) and deserving a less severe punishment (Mean=7.57, S.D.=2.59) than reckless driving (Mean=9.36, S.D.=1.25; Mean=9.09, S.D.=1.30; respectively). Additionally, the key factor predicting public opinion regarding COVID-19-related misbehaviors was the perceived contribution of these misbehaviors to virus-related morbidity. The perceived contribution to morbidity explained 52% of the variance in the seriousness of misbehavior and 53% of the severity of appropriate punishment Conclusions: The findings suggest that it is critical to advocate for and reinforce the public's understanding of the association between the increase in morbidity and the violation of restrictions preventing the transmission of viruses. Our findings also support the notion that the definitions of "crime" and "deviance" are not inherent or intrinsic but are created by the social context.